Inducing a Nanotwinned Grain Structure within the TiO2 Nanotubes Provides Enhanced Electron Transport and DSSC Efficiencies >10%. Issue 33 (15th October 2018) - So, Seulgi; Hwang, Imgon; Yoo, JeongEun; Mohajernia, Shiva; Mačković, Mirza; Spiecker, Erdmann; Cha, Gihoon; Mazare, Anca; Schmuki, Patrik
Abstract: Titania is one of the key materials used in 1D, 2D, and 3D nanostructures as electron transport media in energy conversion devices. In the present study, it is shown that the electronic properties of TiO2 nanotubes can be drastically improved by inducing a nanotwinned grain structure in the nanotube wall. This structure can be exclusively induced for "single‐walled" nanotubes with a high‐temperature treatment in pure oxygen atmospheres. Nanotubes with a twinned grain structure within the tube wall show a strongly enhanced conductivity and photogenerated charge transport compared to classic nanotubes. This remarkable improvement is exemplified in the electronic properties by using nanotwinned TiO2 nanotubes in dye‐sensitized solar cells where a significant increase in efficiency of up to 10.2% is achieved. Abstract : Nanotwinned grain structures in the TiO2 nanotube walls can be induced for "single‐walled" nanotubes via high‐temperature treatment in pure oxygen atmosphere. Such twinned nanotubes show a strongly enhanced conductivity and photogenerated charge transport compared to classical nanotubes and can lead to efficiencies of up to 10.23% in dye‐sensitized solar cells.